2020
DOI: 10.2147/nss.s269360
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inspiratory Muscle Training in the Severity of Obstructive Sleep Apnea, Sleep Quality and Excessive Daytime Sleepiness: A Placebo-Controlled, Randomized Trial</p>

Abstract: Purpose: Exercise programs have been considered as an adjuvant treatment in obstructive sleep apnea (OSA). However, few studies have focused on the effects of the inspiratory muscle training (IMT) in reducing the severity and the symptoms of OSA. Patients and Methods: A randomized controlled trial was conducted and approved by the local Ethics Committee. All subjects signed the informed consent form and were randomized into 2 groups: a) IMT group (n = 8), 8 weeks of IMT with 75% of maximal inspiratory pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(54 citation statements)
references
References 29 publications
(56 reference statements)
3
49
0
2
Order By: Relevance
“…Of these, 12 were excluded for conference abstract, two for wrong intervention, one for wrong population, and one for wrong publication type. Ultimately, eight studies met the criteria for eligibility and were included in the review [ 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. The flow chart of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 12 were excluded for conference abstract, two for wrong intervention, one for wrong population, and one for wrong publication type. Ultimately, eight studies met the criteria for eligibility and were included in the review [ 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. The flow chart of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in the USA [ 17 , 26 ], two in Taiwan [ 23 , 25 ], two in Brazil [ 16 , 21 ], one in Egypt [ 22 ], and one in Turkey [ 24 ]. All studies were published after 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations